Turystyka etniczna a doświadczanie kulturowej inności - Hoffmann, Beata (Studia Etnologiczne i Antropologiczne, 2012)
Relocation in space has accompanied people for ages. Searching for food, new possibilities of the settlement, work, education or religious cult places have become the aim of first excursions and journeys. It is difficult, though, to regard the communities at that time as travel and their activity as the development of tourism. There exist many definitions of tourism, and the majority of them underlines the importance of a free, and spacious mobility of people connected with changing places of residence, environment or the rhythm of life. Irrespective of definitional propositions, tourism is without a doubt a complex psychological, social, economic, spacious and cultural phenomenon. Special attention is to be paid to connections between tourism and culture. Tourism protects, enriches and popularizes cultural goods while culture inspires the development of tourism. Enabling culture meetings, tourism is becoming a more important factor of cultural changes. A revival of locality, growing criticism of mass civilization, and technizational idealism observed in recent years, formed a type of nostalgia for the past, and influenced a significant growth of interest in cultural, or put it more precisely, ethnic tourism. Ethnic tourisms is identified with alternative, rural, folklore, adventurous or sentimental tourism. Its present shape, however, has become yet another example of cultural non-transparency of modern reality. On the one hand, we observe a clear demand for typical ethnically-foreign tourist elements and a valorization of our own traditions, and a conscious development of a native group identity on the other.